Arthroscopic subacromial decompression in the treatment of shoulder impingement syndrome: a prospective study in Malaysia - Siron @ Baharom, Khairul Nizam; Mat Lani, Muhamad Taufik; Chooi, Leng Low; Ren, Yi Kow (2021)
Introduction Shoulder impingement syndrome (SIS) is one of the common problems which lead to shoulder disabilities. This condition has been described as impingement to the rotator cuff by the anterior third of the acromion process and has been classified into three stages. Treatment option varies depending on the grade of the disease. Arthroscopic subacromial decompression (ASAD) has become more popular in recent years and has shown to have a good outcome. The purpose of this study is to evaluate the outcomes following ASAD in terms of the functional, clinical, and radiological parameters in treating SIS in the ageing population in Kuantan, Pahang, Malaysia. Materials and methods This was an observational study looking at the outcomes of patients with stage 2 and stage 3 (partial cuff tear) impingement syndrome who underwent ASAD in Hospital Tengku Ampuan Afzan and International Islamic University Malaysia Medical Centre from May 2018 to June 2019. The functional outcomes were evaluated using American Shoulder and Elbow Surgeons (ASES) score taken at pre-operative, six weeks, three months, and six months post-operation. Clinical outcomes were evaluated using Constant score (CS) taken at six months post-operation. Radiological outcomes were measured by comparing acromiohumeral distance pre- and post-operation on anteroposterior (AP) view radiograph of the affected shoulder. Results A total of 28 patients were selected for the study. On functional outcome, there was a significant effect of time on the ASES scoring system (p-value <0.05) from pre-operative to six months post-operation. On clinical outcome, the CS at six months showed 13 patients have excellent scores, 10 have good, and five have fair scores. There was a statistically significant difference in mean values of all categories (p-value <0.05). In terms of the radiological outcome, this study observed a significant increase in patients’ subacromial space on X-ray from the pre-operative and post-operative treatment stages. In this study, we also observed that there was no significant difference in outcomes between partial and intact rotator cuff (RC) tears at six- month post-operation. Conclusion In this study, ASAD was found to be a beneficial intervention in the treatment of patients with shoulder impingement evidenced by the significant outcomes in terms of functional, clinical, and radiological parameters.